The expression profile and role of non-coding RNAs in obesity - Ghafouri-Fard, Soudeh; Taheri, Mohammad (European journal of pharmacology, 2021)
Latest years have experienced a dramatic upsurge in the knowledge about the function of non-coding transcripts in the determination of diverse human phenotypes including obesity. Several miRNAs and lncRNAs participate in the regulation of metabolic pathways leading to obesity. Several lncRNAs such as Mist, lincIRS2, lncRNA-p5549, H19, GAS5 and SNHG9 have been shown to be down-regulated in adipose tissues or other biological samples in the obese human or animal subjects. On the other hand, Meg3, Plnc1, Blnc1, AC092834.1, TINCR and PVT1 are among up-regulated lncRNAs in the obese subjects. Tens of miRNAs have differential expression between obese and non-obese subjects or between mature adipocytes and pre-adipocytes. Understanding the molecular mechanism of involvement of non-coding RNAs in the pathobiology of obesity would simplify design of therapeutic choices for protecting against obesity and its related comorbidities. We explain the available literature on the function of these transcripts in the pathobiology of obesity. •Numerous miRNAs, circRNAs and linear lncRNAs participate in the regulation of metabolic pathways leading to obesity.•Meg3, Plnc1, Blnc1, AC092834.1, TINCR and PVT1 are among up-regulated lncRNAs in the obese subjects.•Tens of miRNAs have differential expression between obese and non-obese subjects or between mature adipocytes and pre-adipocytes.•Understanding the ceRNA network would simplify design of therapeutic choices for protecting against obesity and its related comorbidities.